The University of the Philippines cultural dictionary for Filipinos - Kintanar, Thelma B. (University of the Philippines Press [and] Anvil Pub., 1996)
This cultural dictionary is a useful reference and guide to students, teachers, parents, supervisors, executives and leaders in different fields. It is considered as an initial inventory of the Philippines' common knowledge and information to help the readers participate in national dialogues and discussions of public discourse on matters that concern them.